Emotional intelligence for management in times of change (Revista Electrónica REDINE, 2017)
Emotional intelligence is a balance of control and regulator of one's own feelings, and of others, because it guides the thinking, rethinking and acting of the individual, extending to the management task in the university institutions. However, many university managers profess to be unfamiliar with this subject. From there, this documentary study has the purpose of analyzing the emotional intelligence in the human resource for management in times of change. The techniques and instruments used were the bibliographic records and the logbook framed in the theoretical revision of its main authors more representative like Goleman (2008). Forming the corpus of research with the components of emotional intelligence in the educational management. By the way, the behavioral characteristics of those who exercise this type of management in these times of change must be related to emotional abilities, based on Emotional Intelligence, which is the individual's ability to recognize and control his own feelings, sustain a Empathic attitude and manage interpersonal relationships. It was concluded the use of emotional intelligence generates in the human being satisfaction and their performances are effective at achieving, university change management It was concluded that the application of emotional intelligence by generating full human and effective
Keywords: intelligence; emotional; management; change; university